The Success of E-Government as A Public Service System in South Bengkulu Regency - Herpita Wahyuni; Ulung Pribadi; Danang Eko Prastya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This research aims to see how well E-government is as a public service system in South Bengkulu Regency. Testing five hypotheses, namely: ease of use of E-government, the benefits of using E-government, security risks, privacy security risks that affect public trust in the government, and trust in government has a positive and significant effect on intentions to use E-government. The research method uses quantitative research methods by distributing questionnaires in the South Bengkulu Regency and analysis of data testing using Smart PLS. The results of the hypothesis test prove that there are three rejected hypotheses, namely: ease of use, benefits of use, and security risks to government trust, while the two accepted hypotheses are: privacy security risks which influence public confidence in the government, and trust in the government has a positive and significant effect against the intention of using E-government.